Dynamics of macroeconomic uncertainty on economic growth in the presence of fiscal consolidation in South Africa from 1994 to 2022 - Eugene Msizi Buthelezi (Economies, 2023)
This paper investigates the effects of macroeconomic uncertainty on economic growth in the presence of fiscal consolidation in South Africa. Markov-switching dynamic regression (MSDR) and time-varying parameter vector autoregression (TVP-VAR) were performed using time series data from 1994 to 2022. Less attention has been given directly to the investigation of macroeconomic uncertainty in different regimes of economic growth in South Africa. Three states are found for economic growth, with mean growth rates of negative 6.29% and positive 3.90% and 1.47%, respectively. Macroeconomic uncertainty was found to have a negative impact of 6.72%, 4.38%, and 3.08% in states 1 to 3, respectively. Fiscal consolidation provided an accommodative policy, as it reduced the negative impact of macroeconomic uncertainty by 3.17%, 1.80%, and 0.92% in states 1 to 3, respectively. However, fiscal consolidation does not completely reduce the negative impact of macroeconomic uncertainty. The transition probabilities of economic growth moving and returning to the same states are 29.46%, 34.07%, and 58.02%, in each state, respectively. The time-varying impulse response functions showed that the shock of macroeconomic uncertainty harms economic growth. Nevertheless, the multiplier effect is not large; however, the economy operates below equilibrium and does not restore equilibrium after the effect of macroeconomic uncertainty. This reflects that it takes time for macroeconomic uncertainty to filter out of the South African economy. It is recommended that fiscal consolidation be considered as an accommodative fiscal policy to reduce macroeconomic uncertainty but not as a main policy for economic growth.
Keywords: E06; E61; E62; F43; F62; 330; fiscal consolidation; macroeconomic uncertainty; economic growth; cyclical adjusted primary balance (CAPB); Markov-switching dynamic regression (MSDR); time-varying vector autoregressive (TA-VAR)